W-Chirped optical solitons and modulation instability analysis of Chen-Lee-Liu equation in optical monomode fibres - İnç, Mustafa; Yakada, Salathiel; Bienvenu, Depelair; Betchewe, Gambo; Chu, Yu-Ming (De Gruyter Poland Sp Z O O, 2021)
This work was devoted to unearth W-chirped to the famous Chen-Lee-Liu equation (CLLE) in optical monomode fibres. The results obtained will be useful to explain wave propagating with the chirp component. To attempt the main goal, we have used the new subordinary differential equation (ODE) technique which was upgraded recently by Zayed EME, Mohamed EMA. Application of newly proposed sub-ODE method to locate chirped optical solutions to the Triki-Biswas equation equation. Optik. 2020;207:164360. On the other hand, we have used the modulation analysis to study the steady state of the obtained chirped soliton solutions in optical monomode fibres.
Keywords: W-chirped solitons; Chen-Lee-Liu equation; modulation instability